Separation and Fractionation of Phenolic Compound (Gallic Acid) from Selected Herbs and β-Glucans from Oat - Che Husain, Nurul Hazwani (IRC, 2016)
The study are related to the extraction of phenolic compound (gallic acid) and β-glucans. Gallic acid claimed to possess antioxidant behaviour and free radical scavengers which aids in lowering the blood glucose level. β-glucans also proved to have significant impacts in preventing the Diabetes Mellitus (DM) complication that might harm the lives of DM patient. Hence, both phenolic compound and β-glucans will be extracted from their species by using water bath shaker. Separation and fractionation of phenolic compound and β-glucans can be performed by using High Performance Liquid Chromatography (HPLC) machine to analyse the desired peak of gallic acid and β-glucans. Methanol and 0.1% phosphoric acid in water will be used as the mobile phase A and B respectively for the HPLC analysis